True yams (Dioscorea): a biological and evolutionary link between eudicots and grasses - Mignouna, Hodeba D.; Abang, Mathew M.; Asiedu, Robert; Geeta, R. (Cold Spring Harbor Laboratory, 2009)
Dioscorea(true yams) is a large genus that contains species important as food (with edible tubers) or as sources of bioactive substances used in a range of applications.Dioscoreais a major staple food in many parts of the world, especially in West Africa and the Pacific islands, and serves as a famine food in many regions. It is a critically important but neglected crop, which is likely to increase in importance as climate change leads to necessary changes in global food systems. It is a herbaceous, climbing, tropical monocot that looks rather like a dicot, and is part of a lineage that is relatively closely related to the phylogenetically derived group containing the grasses. Therefore, it represents an important biological link between the eudicots and grasses--groups that contain all the model flowering plant species--and has the potential to fill gaps in our knowledge of plant biology and evolution. Yams also offer us the possibility to gain new insights into processes such as tuberization and sex determination, which cannot be studied in current model organisms. This combination of rising importance due to its socioeconomic significance and interesting biology and evolutionary position justify its potential as a model organism. This potential remains to be harnessed, and much of the current work on yam is directed toward its role as a food crop. This aspect will remain important, but its potential for answering questions of basic biological interest will be a major motivation for researchers interested in this organism.